2018
DOI: 10.1093/jxb/ery169
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate signalling in the regulation of rubber biosynthesis in laticifer cells of rubber tree, Hevea brasiliensis

Abstract: Rubber trees are the world's major source of natural rubber. Rubber-containing latex is obtained from the laticifer cells of the rubber tree (Hevea brasiliensis) via regular tapping. Rubber biosynthesis is a typical isoprenoid metabolic process in the laticifer cells; however, little is known about the positive feedback regulation caused by the loss of latex that occurs through tapping. In this study, we demonstrate the crucial role of jasmonate signalling in this feedback regulation. The endogenous levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 71 publications
0
64
0
Order By: Relevance
“…However, the tools developed to date are limited to the upregulation of plant defense responses against necrotrophic pathogen or insect attack, and although these are important, more versatile tools such as those that are able to improve the efficiency of plant growth are highly desirable. One research priority is a tool that is able to upregulate [79] secondary metabolite production in medicinal plants without concomitant growth inhibition [81,82], and recent studies have revealed the relationship between jasmonate signaling and transcription factors (TFs), which govern the biosynthetic genes of secondary metabolites [83,84]. Thus, chemical control of individual TF or JAZs in the upstream pathway could be an efficient strategy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the tools developed to date are limited to the upregulation of plant defense responses against necrotrophic pathogen or insect attack, and although these are important, more versatile tools such as those that are able to improve the efficiency of plant growth are highly desirable. One research priority is a tool that is able to upregulate [79] secondary metabolite production in medicinal plants without concomitant growth inhibition [81,82], and recent studies have revealed the relationship between jasmonate signaling and transcription factors (TFs), which govern the biosynthetic genes of secondary metabolites [83,84]. Thus, chemical control of individual TF or JAZs in the upstream pathway could be an efficient strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced in vitro rubber biosynthesis of latex from tapped trees is closely associated with the up-regulation of the genes encoding the key enzymes for rubber biosynthesis by activating jasmonate signalling [14]. It may also be related to the changes in the key enzyme activity by phosphorylation modification.…”
Section: Discussionmentioning
confidence: 99%
“…In natural rubber production, the milky latex is obtained by successive tapping, a process of artificially severing the laticifer rings every 2-3 days [13]. Latex exploitation by tapping enhances latex regeneration and the efficiency of natural rubber biosynthesis by activating jasmonate signalling in laticifers [14]. To increase the tapping efficiency, ethrel is applied to increase the rubber yield per tapping to economize on tapping workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is an important rubber-producing plant of Euphorbiaceae [1,2]. The valuable of rubber tree as a sole commercial source rubber-producing plant led to enormous interest in understanding the natural rubber biosynthesis and regulation [3][4][5]. Natural rubber (NR) is regarded as a valuable industry raw material which is synthesized in latex of laticifers [6,7].…”
Section: Introductionmentioning
confidence: 99%